2020
DOI: 10.31643/2020/6445.29
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining hydroxyapatite coatings by mechanochemical interaction

Abstract: The research represents a newly-developed simple method to apply hydroxyapatite by gas-dynamic spraying. The hydroxyapatite coating formed on VT1-0 titanium were obtained following the mechanochemical interaction of hydroxyapatite and titanium with gas-dynamic spraying. The article proposes the phase composition, surface morphology, and roughness of these coatings. The surface morphology of the hydroxyapatite coating had a porous structure. The transverse sections of coatings were researched to study the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As can be seen from the friction results without lubrication, the TiAlCN-2 coating has the lowest and most stable CoF compared to the other coatings, indicating that this coating has low friction resistance [ [29][30][31][32]]. In addition, low CoF can be associated with the formation of debris in the wear track, which leads to the subsequent formation of a lubricating transition layer, mainly due to an increase in carbon sp 2 [33].…”
Section: Research Discussionmentioning
confidence: 99%
“…As can be seen from the friction results without lubrication, the TiAlCN-2 coating has the lowest and most stable CoF compared to the other coatings, indicating that this coating has low friction resistance [ [29][30][31][32]]. In addition, low CoF can be associated with the formation of debris in the wear track, which leads to the subsequent formation of a lubricating transition layer, mainly due to an increase in carbon sp 2 [33].…”
Section: Research Discussionmentioning
confidence: 99%
“…All six powder mixtures were completely transformed into HA with crystallite sizes ranging from 18.5 to 20.2 nm after 1 h and from 22.5 to 23.9 nm after 2 h of grinding. In [21], hydroxyapatite coatings on titanium were obtained after mechanochemical interaction by the gas-dynamic spraying method. The results of cross-sections of coatings showed that the formation of HA particles predominantly occurred in the depressions of the titanium substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods are used to apply CaP coatings, including typical methods such as the sol-gel method [12], plasma spraying [13], electrophoretic deposition [14], micro-arc oxidation (MAO) [15], chemical vapor deposition [16], pulsed laser deposition [17], ion beam deposition [18], magnetron sputtering [19], and sandblasting [20,21], among others. Some researchers [22,23] have proposed a combination of methods for the deposition of CaP coatings.…”
Section: Introductionmentioning
confidence: 99%